Cover Image. Issue 8 (29th September 2021) - Sclocco, Roberta; Nguyen, Christopher; Staley, Rowan; Fisher, Harrison; Mendez, April; Velez, Christopher; Kettner, Norman W.; Kuo, Braden; Napadow, Vitaly
Abstract : The cover image is based on the Original Article Non‐uniform gastric wall kinematics revealed by 4D Cine magnetic resonance imaging in humans by Roberta Sclocco et al., https://doi.org/10.1111/nmo.14146 .